The English novel : an introduction - Eagleton, Terry 1943- (Malden, MA : Blackwell Pub., 2005)
Written by one of the world's leading literary theorists, this book provides a wide-ranging, accessible and humorous introduction to the English novel from Daniel Defoe to the present day.
t
Includes bibliographical references (p. 338-341) and index.
English
Abdul Gani
Keywords: English fiction -- History and criticism; English fiction